Stability Analysis of Saka DAM Diversion Tunnel Portal - Febrie Maulana Fajrin; Subagyo Pramumijoyo; I Gde Budi Indrawan (Journal of Applied Geology, 2023)
The Saka Dam has a channel in the form of a diversion tunnel. This paper presents the results of rock mass characterization using the Geological Strength Index (GSI) classification and evaluation of the stability of the tunnel portal slope with earthquake loads using numerical methods. Based on the GSI classification, the Saka Dam tunnel portal slope is composed of rock masses that are poor quality, fair, and good. The calculation results show the Saka Dam can experience earthquake loads with an acceleration value of 0.4g. Earthquake loads can cause a decrease in the safety value (SRF) of the tunnel portal slope based on the results of numerical analysis. SRF value of natural portal slope without earthquake effect is 10.23 (inlet) and 1.5 (outlet). SRF value of the design slope portal without earthquake effect is 6.64 (inlet) and 1.76 (outlet), whereas if the earthquake effect is taken into account the SRF value obtained is 20.31 (inlet) and 0.99 (outlet). This shows that the condition of the natural portal slope and the portal slope design planner section of the Saka Dam inlet diversion tunnel is in the safe category. Meanwhile, for the portal slope excavated from the outlet section, modification is needed to obtain a safe slope condition. The results of the modified geometry of the slopes at the outlet section resulted in an SRF value of 1.47 which indicates the slope is stable